Menyoroti Kinerja Majelis Pengawas Daerah dalam Pengawasan Notaris di Gorontalo Utara - Sri Indriyanti Mahmud; Novendri Nggilu; Nur Mohamad Kasim (Indonesia Law Reform Journal, 2021)
The purpose of this study is to know and conduct an analysis of the function of the Regional Supervisory Assembly in notary supervision in North Gorontalo Regency and the obstacles faced by the regional supervision assembly in conducting notary supervision in North Gorontalo Regency? This research uses a type of normarif-empirical research using the Statute Approach;and CaseApproach. the results of this study show, that first, the function of the regional supervision assembly in notary supervision in North Gorontalo Regency is the same as regional supervision assemblies throughout Indonesia it is divided into two, namely the construction of its intent for preventive measures to prevent violations to be committed by a notary, and supervision is an essive re-pr actas aresult of the non-enactance of preventive measures in the construction. Second, the obstacles faced by the regional supervision assembly in conducting notary supervision in North Gorontalo Regency are: First, sanctions to the notary from the regional supervisor and from the center, second, not only notary when done coaching and supervision, the third, namely communication errors that cause problems become greater. Keywords: Regional Supervisory Council; Supervision; Coaching; Notary Public   Abstrak Tujuan penelitian ini adalah untuk mengentahui dan melakukan analisis terhadap fungsi Majelis Pengawasan Daerah dalam pengawasan notaris di Kabupaten Gorontalo Utara dan kendala yang dihadapi majelis pengawasan daerah dalam melakukan pengawasan notaris di Kabupaten Gorontalo Utara? Penelitian ini menggunakan jenis penelitian normarif-empiris dengan menggunakan pendekatan Undang-Undang (Statute Approach); dan Pendekatan kasus (Case Approach). hasil Penelitian ini menujukkan, bahwa Pertama, Fungsi majelis pengawasan daerah dalam pengawasan notaris di Kabupaten Gorontalo Utara sama seperti majelis pengawasan daerah di seluruh indonesia hal itu terbagi dua yaitu pembinaan maksudnya untuk tindakan preventif guna mencegah pelanggaran-pelanggaran yang akan dilakukan oleh notaris, dan pengawasan adalah tindakan represif sebagai akibat dari tidak diindahkannya tindakan preventif dalam pembinaan. Kedua, kendala yang dihadapi majelis pengawasan daerah dalam melakukan pengawasan notaris di Kabupaten Gorontalo Utara adalah; pertama, sanksi kepada notaris itu dari pengawas wilayah dan dari pusat, kedua, tidak kopertaifnya notaris ketika dilakukan pembinaan dan pengawasan, yang ketiga, yaitu kesalahan komunikasi sehingga menyebabkan masalah menjadi lebih besar.